Effect of Starch Nanocrystal on the Properties of Carbon Black-Natural Rubber Composites - Gao, Y.J.S.; Fang, L.; Li, S.D.; Li, L.F.; Liao, S.Q.; Wang, Z.F. (Asian Journal of Chemistry, 2014)
Starch nanocrystals (SNC) is the representative of a new class of fillers. In our work SNC were prepared by acidolysis. The starch nanocrystal-carbon black-natural rubber (SNC/CB/NR) composites were obtained by blending CB/NR master batch with SNC/NR master batch in the open mill. The effectof SNC on the properties of CB/NR composites was investigated. The results showed that mechanical properties decreased with the increasing content of the SNC. The abrasion surface was observed by scanning electron microscopy and the abrasion surface of samples were much rougher. Thermal analysis presented that the glass transition temperature and the endothermal peak decreased gradually with the increment of SNC and the thermal degradation reaction of SNC/CB/NR composites was two-step reaction. The curves of G' and tan d versus strain of vulcanization were presented by rubber process analyzer, respectively. Dynamic mechanical thermal analysis showed that the loss factor at 0 ºC, SNC increased and decreased at 60-80 ºC by adding SNC.